Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Section 10.7 - Complex Numbers - Exercise Set - Page 741: 102



Work Step by Step

$(8-\sqrt {-4})-(2+\sqrt {-16})$ =$(8-\sqrt {-1\times4})-(2+\sqrt {-1\times16})$ =$(8-\sqrt {-1}\sqrt 4)-(2+\sqrt {-1}\sqrt {16})$ =$(8-i\sqrt 4)-(2+i\sqrt {16})$ =$(8-2i)-(2+4i)$ =$8-2i-2-4i$ =$8-2-2i-4i$ =$6-6i$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.